Electric-Shock Weapons, Tasers and Policing Myths and Realities - Dymond, Abi (Routledge Studies in Policing and Society, 2022)
Building on five years of research, and drawing on criminology, science and technology studies (STS), socio-legal studies and social psychology, this book is the first non-medical book written on electric-shock weapons, of which the best well known is the TASER brand. The police's ability to use force is one of their most crucial powers, yet one that has been relatively neglected by criminology. This book challenges some of the myths surrounding the use of these weapons and considers their human rights implications and impact on members of the public and officers alike. Drawing on STS, it also considers the role and impact of electric-shock technologies, examines the extent to which technologies and non-human agency may also play a role in shaping officer decision making and discretion, and contributes to long standing debates about police accountability. This is essential reading for policing scholars around the world, particularly those engaged with use of force, culture and accountability, as well as those engaged with Science and Technology studies.